A STUDY ON THE STANDARDIZATION PARAMETERS OF BAUHINIA VARIEGATA - Khare, Pragati; Kishore, Kamal; Sharma, Dinesh Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: In today's scenario, the herbal medicines are much efficient for the treatment of various disorders as they have minimal side effects in comparison to the allopathic medicines. Bauhinia variegata L. (Mountain Ebony), commonly called Kachnar, belongs to the family Leguminosae. It is a medium-sized tree, mostly found at an altitude of 1300 m in the Himalayas. The objectives of the present study are to investigate various pharmacognostic, phytochemical analysis, and pharmacological properties of B. variegata. Methods: The powdered drug was used for estimating the loss on drying, ash values, fluorescence studies, chemical tests, and extractive values. Macroscopic and microscopic studies were also performed. Results: The leaf microscopy revealed the presence of upper and lower epidermis, palisade tissue, well-developed vascular bundle. The fluorescence characteristics of leaf powder were studied both in visible light and ultraviolet light (254 nm and 365 nm) after treatment with various reagents. Kachnar is composed of carbohydrates, tannins, alkaloids, flavonoids, amino acid. It was reported that the total ash value was 8.15%. The acid insoluble ash value was 5.5%. Conclusion: The main pharmacological activities of B. variegata are anthelmintic, antiulcer, antitumor, antimicrobial, antidiabetic, anti-inflammatory,Â antigoitrogenic, and hepatoprotective. The present investigation provides the information on its pharmacognostic, phytochemical analysis, and pharmacological properties. Keywords: Flavonoids, Kachnar, Alkaloids, Antioxidant, Leguminosae.